2020
DOI: 10.1016/j.cell.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Processing of lncRNAs Contributes to Non-conserved Functions in Stem Cells

Abstract: Highlights d Subcellular localization of conserved lncRNAs is different in hESCs and mESCs d Cytoplasmic hFAST but not nuclear mFast promotes WNT signaling in hESC pluripotency d PPIE regulates distinct FAST processing in hESCs and mESCs d RNA processing and localization contribute to lncRNA functional evolution

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
157
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(177 citation statements)
references
References 80 publications
6
157
0
Order By: Relevance
“…However, lncRNAs are among least well-understood ncRNAs. This is probably due to the variety of regulatory mechanisms that they could affect [16], but also to their rapid evolution, and consequently, to the absence of recognisable homologs for most of the lncRNAs even in evolutionarily close species [17,18] and to the divergent subcellular location and function of certain conserved lncRNAs [19]. LncRNAs regulate the expression of adjacent genes (cis-acting regulation) or genes located at other genomic locations, even on different chromosomes (trans-acting) [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lncRNAs are among least well-understood ncRNAs. This is probably due to the variety of regulatory mechanisms that they could affect [16], but also to their rapid evolution, and consequently, to the absence of recognisable homologs for most of the lncRNAs even in evolutionarily close species [17,18] and to the divergent subcellular location and function of certain conserved lncRNAs [19]. LncRNAs regulate the expression of adjacent genes (cis-acting regulation) or genes located at other genomic locations, even on different chromosomes (trans-acting) [16].…”
Section: Introductionmentioning
confidence: 99%
“…In fish, although functional studies remain highly limited, several publications reported the modulation of lncRNAs after different stimuli and/or conditions with a special focus on the immune system [19]. Because lncRNAs can alter the expression of their adjacent genes, the functionality of those lncRNAs identified in fish is usually predicted based on the function of their neighbouring protein-coding genes [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, do homologous lncRNAs across species always have the same function? Through systematic high-throughput analysis of sequence and positionally conserved lncRNAs across species, Guo et al [ 119 ] discovered the distinct subcellular localization and function of the lncRNA FAST (FOXD3 anti-sense transcript 1) in human and mouse embryonic stem cells (ESCs). In human ESCs, FAST is mainly expressed in the cytoplasm, where it blocks the interaction of the ubiquitin ligase β-TrCP (transducin repeats-containing protein) with phosphorylated β-catenin, leading to the prevention of β-catenin degradation, activation of WNT signaling, and maintenance of pluripotency.…”
Section: Evolutionary Conservation and Tissue Specificity Of Lncrnmentioning
confidence: 99%
“…Moreover, lncRNAs have great significance in regulating the fate of stem cells, such as maintaining cellular pluripotency [ 9 ]. By carrying out high-throughput sequencing analysis of RNA derived from the nucleus and cytoplasm of embryonic stem cells (ESCs), Guo et al [ 10 ] found that there were significant differences in the processing and subcellular localization of lncRNAs between human and mouse ESCs, which led to different biological functions of lncRNAs in the regulation of cellular pluripotency. Recent studies have shown that lncRNAs also play a pivotal regulatory role in the differentiation and development of germ cells.…”
Section: Introductionmentioning
confidence: 99%